Presumptive Analysis of Escherichia coli in Asian Moon Scallop (Amusium pleuronectes) as a Bioindicator of Water Quality in Lampung Bay - Monik, Della Tiara; Karin, Nadia Elvira (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The asian moon scallop (Amusium pleuronectes) is a high-value fishery commodity and serves as a natural bioindicator of water quality due to its filter-feeding behavior. This research aimed to analyze Escherichia coli contamination in scallop products from Lampung Bay as an indicator of microbiological and environmental conditions. Testing was conducted at the Microbiology Laboratory of UPTD PMHP, Lampung Province, using the Indonesian National Standard (SNI) 2332.1:2015. The presumptive test using Lauryl Tryptose Broth (LTB) showed five positive tubes: three at 10⁻¹, one at 10⁻², and one at 10⁻³ dilution. However, confirmatory tests using Brilliant Green Lactose Bile Broth (BGLB), EC Broth, and L-EMB Agar all showed negative results for E. coli, with a Most Probable Number (MPN) value of <3 MPN/g. Environmental quality assessment indicated that physicochemical parameters complied with marine water quality standards. The pH ranged from 7.8–8.0, temperature was 27–30°C, salinity ranged from 30–34 ppt, and DO was >5 mg/L. The results demonstrate that the scallop products are microbiologically safe and that the surrounding waters meet environmental quality standards, supporting sustainable shellfish cultivation. Routine monitoring, enhanced waste management, and fortified bioindicator-based assessments are recommended to ensure long-term food safety and environmental sustainability in coastal regions.